2016
DOI: 10.1016/j.metabol.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet composition on weight loss, metabolic factors and biomarkers in a 1-year weight loss intervention in obese women examined by baseline insulin resistance status

Abstract: Background Obesity is a risk factor for postmenopausal breast cancer incidence and pre- and postmenopausal breast cancer mortality, which may be explained by several metabolic and hormonal factors (sex hormones, insulin resistance, and inflammation) that are biologically related. Differential effects of dietary composition on weight loss and these metabolic factors may occur in insulin-sensitive vs. insulin-resistant obese women. Objective To examine the effect of diet composition on weight loss and metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 41 publications
5
73
1
1
Order By: Relevance
“…Another randomized controlled trial (RCT) in postmenopausal women tested a lower-fat, higher-carbohydrate diet (20% and 65% energy, respectively), a lowercarbohydrate, higher-fat diet (45% and 35% energy, respectively), and a walnut-rich higher-fat, lower-carbohydrate diet (18%, 35%, and 45% energy, respectively) for weight loss. All three diets led to weight loss at 12 months, with slightly higher weight loss in the lower-fat diet group (33). A meta-analysis of dietary intervention trials showed that low-fat diets were effective for weight loss under ad libitum conditions (36); however, this was published prior to recent carbohydraterestricted diet studies.…”
Section: Obesity and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another randomized controlled trial (RCT) in postmenopausal women tested a lower-fat, higher-carbohydrate diet (20% and 65% energy, respectively), a lowercarbohydrate, higher-fat diet (45% and 35% energy, respectively), and a walnut-rich higher-fat, lower-carbohydrate diet (18%, 35%, and 45% energy, respectively) for weight loss. All three diets led to weight loss at 12 months, with slightly higher weight loss in the lower-fat diet group (33). A meta-analysis of dietary intervention trials showed that low-fat diets were effective for weight loss under ad libitum conditions (36); however, this was published prior to recent carbohydraterestricted diet studies.…”
Section: Obesity and Diabetesmentioning
confidence: 99%
“…Conversely, highcarbohydrate diets containing whole grains and other high-fiber foods provide the preferred fuel for colonic bacteria, with less secondary bile acid production and greater production of butyrate and other shortchain fatty acids that lower inflammation, decrease cellular proliferation, and enhance expression of genes with antineoplastic properties. Low-fat diets may also decrease serum estradiol and increase sex hormone-binding globulin (32,33) and may reduce other breast cancer risk factors such as mammographic density (34), although the persistence of these effects remains unclear.…”
Section: The Case For a Low-fat High-carbohydrate Diet Physiologic Mmentioning
confidence: 99%
“…The flow of the study selection procedure which followed the literature search is summarised in Figure 1 Table 2 . Five trials [45][46][47][48][49] did not include LDL-C as an outcome; ten trials [50][51][52][53][54][55][56][57][58][59] were performed on participants with Diabetes mellitus and/or CVD; eleven trials [60][61][62][63][64][65][66][67][68][69][70] had less than 100 randomised participants; three [71][72][73] had duration < 6 months; two trials 74,75 did not report on SD or 95% CI; seven trials [76][77][78][79][80][81][82] were irrelevant with inappropriate intervention; and one trial 83 was dismissed based on high attrition rate and high risk of bias.…”
Section: Literature Searchmentioning
confidence: 99%
“…Tindall et al, 2019 [9] found no association between nut consumption and fasting glucose (weighted mean difference (WMD)-0.52 mg/dL (0.028 mmol/L); 95% CI −1.43, 0.38 mg/dL; I 2 = 53.4%) from a meta-analysis of 39 RCTs [58,61,63,[66][67][68]74,78,80,83,86,. Tindall et al, 2019 [9] found no effect of nut consumption on HbA1c (WMD 0.02%; 95% CI −0.01%, 0.04%; I 2 = 51.0%).…”
Section: Glycemic Controlmentioning
confidence: 99%
“…Tindall et al, 2019 [9] found no effect of nut consumption on HbA1c (WMD 0.02%; 95% CI −0.01%, 0.04%; I 2 = 51.0%). Tindall et al, 2019 [9] observed significant reductions in homeostasis model assessment of insulin resistance (HOMA-IR) (WMD −0.23; 95% CI −0.40, −0.06; I 2 = 51.7%) and fasting insulin (WMD −0.40 µIU/mL; 95% CI −0.73, −0.07 µIU/mL; I 2 = 49.4%) after nut consumption from meta-analyses of 19 RCTs [61,66,68,74,86,91,92,96,97,99,100,[103][104][105]107,109,110,114,117] and 28 RCTs [58,61,63,[66][67][68]74,86,[91][92][93][95][96][97][99][100][101][102][103][104][105]107,110,[112][113][114]...…”
Section: Glycemic Controlmentioning
confidence: 99%